CALCB splice region pathogenic variants leading to plasma cell neurotropic enrichment in type 1 autoimmune pancreatitis - Liu, Qi-cai; Chen, Falin; Wu, Chao-yang; Gao, Feng; Zhuang, Ze-hao; Chen, Jin-tong; Cai, Bin; Zhang, Tianming; Guo, Ling; Lin, Li-qing; Zhao, Cheng-fei; Lin, Xin-hua (Cell death & disease, 2017)
Recently, we have demonstrated that PRSS1 mutations cause ectopic trypsinogen activation and thereby result in type 1 autoimmune pancreatitis (AIP). However, the molecules involved in inducing obliterative vasculitis and perineural inflammation in the pancreas are not well-described. The present study applied whole-exome sequencing (WES) to determine the underlying etiology and revealed novel missense splice region variants, CALCB c.88T>C (p.Ser30Pro) and IR [1]-mutants, in 2 of the 3 families and 2 of 26 unrelated patients with type 1 AIP. In vitro , both of the mutants displayed decreased βCGRP, ERK1/2 phosphorylation, and co-localized with endoplasmic reticulum and Golgi apparatus. The novel pathogenic variant identified in this case should contribute to our understanding of the expanding spectrum of AIP.